A multi-scale synthetic eddy method for generating inflow data for LES. (12th October 2017) - Luo, Yin; Liu, Hongjun; Huang, Qin; Xue, Huili; Lin, Kun
Highlights: A multi-scale SEM method is developed to generate self-sustaining turbulence. The proposed method prescribes both coherent structures and turbulence spectra. The eddies in the proposed method vary with the distance from the wall. The eddies in the proposed method are convected with a local mean wind speed. Abstract: A multi-scale synthetic eddy method (MSSEM) for generating inflow turbulence that approaches realistic turbulence characteristics is presented. The proposed method is a modified version of the synthetic eddy method (SEM), which regards turbulence as a superposition of coherent structures. The inflow turbulence generated by the SEM can match the prescribed first and second statistical moments, length scales, and autocorrelation functions, but it cannot match the turbulence spectrum, which is a key characteristic of turbulence. The idea of the MSSEM is to introduce multi-scale eddies with spectrum energies with a focus on different frequency ranges and then synthesize eddies with different scales and energies to match the objective spectrum. The length and proportion of each scale eddy are determined with a predefined turbulence length and turbulence spectra. The advection velocity of a multi-scale eddy is the mean wind value at the location of the eddy and not the constant wind speed. Three large eddy simulations of a turbulent boundary layer with inflow turbulence generated by Lund's method, SEM and MSSEM are considered in this study. The turbulence characteristics at the inlet plane and in the internal flow field are compared and discussed. Result shows that the turbulence structure in the case of the MSSEM resembles turbulence, and the turbulence spectra of three velocity components show good agreement with the predefined values at the inlet plane and in the internal flow field.